Micelle delivery of doxorubicin increases cytotoxicity to prostate carcinoma cells - McNealy, Tamara Lyn; Trojan, Lutz; Knoll, Thomas; Alken, Peter; Michel, Maurice Stephan (Urological research, 2004)
The use of doxorubicin as a chemotherapeutic agent is hindered by its toxic side effects on the normal cells of the body. The objective of this study was to determine if micelle-delivered doxorubicin could increase the effectiveness of doxorubicin against prostate carcinoma cells. Rat prostate carcinoma cells (MatLu) were cultured under standard conditions. Phosphate-buffered saline (PBS), doxorubicin and/or micelle solution (Pluronic 10500 solution) was added to the cell suspensions and incubated for 3 h. After incubation, cells were washed twice. Analysis consisted of: 1) immediate cell count and 2) proliferation assay at 24 and 144 h. After 24 h, samples with micelle-incorporated doxorubicin had 75% (10% pluronic with 10 µg/ml doxorubicin) and 80% (1% pluronic with 10 µg/ml doxorubicin) cell proliferation results compared with the control group. After 144-h incubation, these same two groups demonstrated cell proliferation results of only 30 and 43% of the control group. The in vitro cytotoxicity of doxorubicin against prostate carcinoma cells was dramatically increased by incorporating the molecule with polymeric micelles.